Revision of Eccoptolonthus Bernhauer (Coleoptera: Staphylininae: Philonthina) with descriptions of four new species from China - Fei, Xu-Dong; Zhou, Hong-Zhang (Zootaxa, 2021)
This study revises the taxonomy of the genus Eccoptolonthus Bernhauer, 1912 and reports 14 species in the Chinese fauna. A catalogue of the remaining 15 Eccoptolonthus species from the Oriental and Afrotropical regions is also provided. Four new species are described from China: Eccoptolonthus conaensis Fei & Zhou, sp. nov. from Tibet, Eccoptolonthus fuyuensis Fei & Zhou, sp. nov. from Zhejiang, Eccoptolonthus dafoensis Fei & Zhou, sp. nov. from Guizhou, and Eccoptolonthus xiaolongmenensis Fei & Zhou, sp. nov. from Beijing. Eccoptolonthus (Eumorimotous) laevigatus laevigatus (Fauvel, 1895) is reported for the first time from Yunnan in China and Vietnam. A preliminary key to the Chinese species of Eccoptolonthus is also included in the paper. Color images and line drawings are provided to show diagnostic characters.